Quality Work Life dan Kepuasan Kerja Perawat di Rumah Sakit Amelia Pare - Nian Afrian Nuari (STIKes Patria Husada Blitar, 2016)
Job satisfaction is a feeling of love or satisfied of the work that is experienced by the individual. This has an impact on the sustainability of the health services and hospital operation. Therefore, the management of the hospital is supposed to power our quality of work life (QWL) in order to avoid a decrease in job satisfaction which will has impact on the performance and results. The purpose of this research was to identify the correlation of quality of work life with job satisfaction of nurses in Amelia Hospital Pare. The research method was correlational study with purposive sampling and sample of 30 respondents. The intruments used questionnaires then analyzed by spearman rho test. Based on the results, the majority (60%) 18 respondents had a quality of work life and job satisfaction in category of very good, almost half (30%) 9 respondents had a quality of work life and job satisfaction in category of good and a small number (10%) 3 respondents had a quality of work life in category quite good. The results of the research obtained p value = 0,007, Ã¡ = 0,05, and cc = 0,479, H1 was accepted. This means that there was a correlation between quality of work life with job satisfaction of nurses in Amelia Hospital Pare with average correlation level. It was expected to achieve optimal health and performance or satisfactory work in the hospital. It was also expected to apply and pay attention to quality ofwork life to increase job satisfaction of nurses, so the purpose of the nurses and the hospital will be achieved.